Healthy lifestyle intervention for adult clinic patients with type 2 diabetes mellitus - Coughlin, Steven S (Diabetes Manag (Lond), 2017)
BACKGROUND: Diet and exercise therapy have been reported to be effective in improving blood glucose control and are an important part of treatment of type 2 diabetes mellitus. OBJECTIVE: The goal of this study is to examine the efficacy of a healthy lifestyle intervention for adult clinic patients with type 2 diabetes mellitus, as measured by Hgb-A1c, cardiovascular indicators, physical activity, weight, and BMI. Also of interest are optimal strategies for subject recruitment, the number of intervention sessions attended, and participant use of the Fitbit watch to monitor their physical activity and track food and beverage consumption. METHODS: A pre/post-test design will be used in this pilot study. Non-institutionalized adult patients (n=50) aged 18–65 years who have been seen at the Augusta Health outpatient clinics (General Internal Medicine or Family Medicine) for type 2 diabetes in the past 12 months, and who are interested in reducing their risk of disease recurrence through healthy lifestyle behaviors, will be eligible to participate. At orientation visit, eligible individuals will be asked to provide written informed consent. Consenting volunteers (n=50) will be asked to complete the baseline and 6-month follow-up questionnaire and to participate in 12 weekly group sessions of 90 min duration, involving physical activity and to meet with a dietitian (baseline, one month, 90 days) to receive individualized advice on diet and nutrition. The technology–based intervention will use wrist-worn Fitbit Blaze physical activity monitoring devices. CONCLUSIONS: This pilot study will provide important information about the feasibility and preliminary efficacy of a healthy lifestyle intervention for adult clinic patients with type 2 diabetes mellitus. The use of consumer-facing devices such as the Fitbit watch has the potential advantage over the use of research accelerometers, pedometers, or actigraphs in increasing the likelihood that the intervention will be sustainable after the study ends.